Artificial Intelligence in Accounting Practice: An Interdisciplinary Review of Technological Innovation and Its Socio-Economic Implications - Abdulrahman Abdulganiyu; Sulaiman Taiwo Hassan (Marasofi International Media and Publishing (MIMP), 2025)
The accounting profession is undergoing significant transformation due to the advancements and integration of Artificial Intelligence (AI), which offers opportunities to enhance and restructure various accounting tasks. A crucial factor in this shift is the ability of accountants to rapidly adjust to these changes by developing the essential skills and knowledge required to effectively collaborate with AI technologies, while also addressing concerns about job security. This study aims to explore the influence of Artificial Intelligence on accounting by conducting a systematic review of existing literature. Results indicate that although current accounting practices incorporate technology to streamline processes and boost efficiency, there is concern that limited AI proficiency may reduce job prospects for accountants. This research contributes valuable insights into the challenges and potential advantages AI poses for the profession. It also emphasizes the need for proactive measures to equip future accountants for an AI-driven work environment.